Activity and Stability of Trypsin Immobilized onto Chitosan Magnetic Nanoparticles - Jun Sun; Bin Xu; Yu Shi; Lin Yang; Hai-le Ma (Advances in Materials Science and Engineering)
The aim of this study was to develop a thermally and operationally stable trypsin through covalent immobilization onto chitosan magnetic nanoparticles (Fe3O4 @CTS). The successful preparation of the Fe3O4 @CTS nanoparticles was verified by Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and transmission electron microscopy (TEM), which indicated that the prepared Fe3O4 @CTS nanoparticles have superparamagnetic properties, with an average size of approximately 17 nm. Then, trypsin was covalently immobilized onto the Fe3O4 @CTS nanoparticles at a high loading capacity (149.25 mg/g). The FTIR data demonstrated that the trypsin had undergone a conformational change compared with free trypsin, and the Michaelis constant (Km) and the maximum hydrolysis reaction rate (Vmax) showed that the trypsin immobilized on the Fe3O4 @CTS had a lower affinity for BAEE and lower activity compared with free trypsin. However, the immobilized trypsin showed higher activity than free trypsin at pH 6.0 and in alkaline conditions and retained more than 84% of its initial activity at 60°C after 8 h incubation. Its excellent performance across a broader pH range and high thermal stability, as well as its effective hydrolysis of bovine serum albumin (BSA) and its reusability, make it more attractive than free trypsin for application in protein digestion.